MATERI FIQH IBADAH DAN IMPLEMENTASINYA BAGI MAHASISWA JURUSAN SYARIAH STAIN PAREPARE - RAHMAWATI RAHMAWATI; WAHIDIN WAHIDIN; ARIS ARIS (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2015)
This paper examines the fqh of worship material taught in the majors for the implementation of Sharia and Sharia students STAIN Pare Pare. Departing from the issue of the inconsistent portion Islamic students to practice as given in the course of fqh of worship then tickle the writers to explore where the actual need to be addressed so that the material fqh of worship can be implemented continuously. Once analyzed, it was found that the level of understanding by both the students can affecting the level of implementation in practice this material. Although the level of students’ knowledge and understanding of the material is varied but level is directly proportional to its implementation in everyday life. Therefore, the student’s knowledge of the material is more normative model of learning material, the fqh of worship is more oriented towards a philosophical approach. This approach led to the awareness of students to practice religious jurisprudence consistently andcontinuously.